SYMBOLIC MEANINGS OF NUMBERS IN ENGLISH AND UZBEK FOLKLORE AND PAREMIOLOGY - Abdusalomov Doniyor Tog‘ayali o‘g‘li (American Journals, 2026)
This article explores how numbers carry symbolic meanings in the folklore and proverbs of English and Uzbek cultures. Through a cross-cultural comparison, it highlights which numerals, such as 3, 7, 9, 40, recur as “magic” or sacred numbers in each tradition and what cultural values or beliefs they signify. English folklore often emphasizes numbers like three and seven, whereas Uzbek folklore and paremiology frequently feature numbers like seven and fort. Drawing on scholarly sources, the study analyzes specific examples from both cultures’ oral traditions and paremiological corpora, illustrating both similarities and differences. Ultimately, this comparative analysis reveals how numerical symbolism in proverbs and folk narratives encodes each nation’s worldview, moral lessons, and aesthetic preferences.
Keywords: Folklore; Proverbs; Paremiology; Number symbolism; Cultural comparison; English; Uzbek.